2019
DOI: 10.1158/1078-0432.ccr-18-2722
|View full text |Cite
|
Sign up to set email alerts
|

A Phase II Study of Tumor-infiltrating Lymphocyte Therapy for Human Papillomavirus–associated Epithelial Cancers

Abstract: Purpose Cellular therapy is an emerging cancer treatment modality, but its application to epithelial cancers has been limited. This clinical trial evaluated tumor-infiltrating lymphocyte (TIL) therapy for the treatment of patients with metastatic human papillomavirus (HPV)-associated carcinomas. Experimental Design The trial was a phase II design with two cohorts, cervical cancers and non-cervical cancers. Cell infusion was preceded by a lymphocyte-depleting conditioning regimen and followed by systemic high… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
126
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 211 publications
(128 citation statements)
references
References 30 publications
0
126
1
1
Order By: Relevance
“…Efforts to understand the determinants of successful TIL-based therapies have focused on resolving which classes of antigens are recognized by infiltrating T cells in responding patients. These studies have revealed that TIL can recognize a wide spectrum of antigens, including tissue differentiation antigens, 6,168 cancer germline antigens, 12 viral oncoproteins, 12,15 and neoantigens. 5,6,8,[10][11][12]17,169,170 Despite evidence of clinical activity, broad dissemination of TIL therapies has been limited by practical challenges associated with procuring and expanding T cells from surgically obtained samples.…”
Section: Elucidating the Landscape Of Cancer-associated Antigens Rementioning
confidence: 99%
See 1 more Smart Citation
“…Efforts to understand the determinants of successful TIL-based therapies have focused on resolving which classes of antigens are recognized by infiltrating T cells in responding patients. These studies have revealed that TIL can recognize a wide spectrum of antigens, including tissue differentiation antigens, 6,168 cancer germline antigens, 12 viral oncoproteins, 12,15 and neoantigens. 5,6,8,[10][11][12]17,169,170 Despite evidence of clinical activity, broad dissemination of TIL therapies has been limited by practical challenges associated with procuring and expanding T cells from surgically obtained samples.…”
Section: Elucidating the Landscape Of Cancer-associated Antigens Rementioning
confidence: 99%
“…This is particularly true for patients with modestly mutated cancers arising from epithelial organs, collectively the leading causes of adult cancer‐related deaths . Detailed immune monitoring studies of exceptional patient responders to immunotherapy have revealed three critical variables that simultaneously must be satisfied for cancer regression to occur . First, the patient must possess a repertoire of T cells capable of recognizing antigens displayed on the surface of cancer cells.…”
Section: Introductionmentioning
confidence: 99%
“…Recent reports have demonstrated that TIL therapy can deliver a significant reduction in tumour burden in late-stage cancer patients suffering from a diverse set of epithelial tumours as well as melanoma. A response rate of 28% was reported in 18 patients with human papilloma virus (HPV)-related cervical cancer using HPV-targeted T cells [34], two of whom had achieved ongoing durable CRs for over 4 years at the time of the report. In an ongoing study of TIL therapy, a 44% response rate, with two CRs, was observed among 27 patients with advanced recurrent, metastatic or persistent cervical cancer [35].…”
Section: Tablementioning
confidence: 99%
“…KRAS and EGFR mutations are essentially restricted to lung adenocarcinomas, and EGFR mutations are enriched in females and non-smokers [59][60][61]. Notably, the tumour mutation burden is markedly lower in patients with EGFR, ALK, RET or ROS1 mutations [34].…”
Section: Genetic Landscape Of Nsclc and Emerging Importance Of Clonalmentioning
confidence: 99%
“…Clinical activity has been reported with tumor-infiltrating lymphocytes for melanoma 3 and for human papillomavirus (HPV)-associated epithelial cancers. [4][5][6] T cell receptor genetically engineered T cells (TCR-T cells) have shown clinical activity in melanoma, 7 sarcoma, 7 and HPV-associated epithelial cancers. 8 Nonetheless, despite remarkable tumor responses in patients with these cancers and other epithelial cancers, 9 10 enhanced efficacy remains an important goal in the development of cellular therapies.…”
Section: Introductionmentioning
confidence: 99%